Mapping of soil phosphorus and zinc nutrients / Nurul Hana Helmi - Helmi, Nurul Hana (Faculty of Plantation and Agrotechnology, 2018)
In precision agriculture, the knowledge of spatial variability of soil properties is very crucial as well as site specific nutrient management. Reliable and real-time data on soil and crop properties are very important for the development of management practices in accordance with the requirements of a selected soil and crop within specific field units. This is significantly where managing the spatial variability of soil nutrients is crucial to minimize the price expenses, and maximizes crop output. There is a requirement for the utilization of procedures and techniques to optimize chemical or fertilizer application which includes the digital soil mapping and GIS application applied to boost the productivity without environment impact. This study addressed the spatial distribution of available Phosphorus (P) and available Zinc (Zn) nutrients of the soil and the purpose of this study was to map the soil phosphorus and zinc nutrients of the research area. The method of this study firstly was sampling the soil. Next, the soil samples were sent to the laboratory for analysis. After getting the results, it will be added and combined with the waypoint list and matched it with the respective waypoint. Then, the result be added and displayed in an ArcMap 10.3 so that be able to see the nutrients values that based on spatial locations and include it in the spatial analysis. Results showed that data collection was required to capture the spatial variability of soil nutrients. From the result, the map shows that the area is less fertile due to only small areas which have the highest Phosphorus concentration value and Zinc concentration value. It is meant that the potential yield that will produce is lower because only the small area is fertile. Applying organic matter is one of a way to increase the availability of Phosphorus and Zinc nutrients of soil. Such results allowed us to conclude that, cost-effective and efficient multi-source data for Digital Soil Mapping (DSM) used to characterize the spatial variability of soil nutrient, to display the spatial dynamics of soil nutrient, and to spatially estimate potential crop yield. These results will guide future spatial sampling of the Phosphorus (P) and Zinc (Zn) supply, and soil monitoring in general.